Evidence for Novel Pharmacological Sensitivities of Transient Receptor Potential (TRP) Channels in Schistosoma mansoni. - Swarna Bais; Matthew A Churgin; Christopher Fang-Yen; Robert M Greenberg (Public Library of Science (PLoS), 2015)
Schistosomiasis, caused by parasitic flatworms of the genus Schistosoma, is a neglected tropical disease affecting hundreds of millions globally. Praziquantel (PZQ), the only drug currently available for treatment and control, is largely ineffective against juvenile worms, and reports of PZQ resistance lend added urgency to the need for development of new therapeutics. Ion channels, which underlie electrical excitability in cells, are validated targets for many current anthelmintics. Transient receptor potential (TRP) channels are a large family of non-selective cation channels. TRP channels play key roles in sensory transduction and other critical functions, yet the properties of these channels have remained essentially unexplored in parasitic helminths. TRP channels fall into several (7-8) subfamilies, including TRPA and TRPV. Though schistosomes contain genes predicted to encode representatives of most of the TRP channel subfamilies, they do not appear to have genes for any TRPV channels. Nonetheless, we find that the TRPV1-selective activators capsaicin and resiniferatoxin (RTX) induce dramatic hyperactivity in adult worms; capsaicin also increases motility in schistosomula. SB 366719, a highly-selective TRPV1 antagonist, blocks the capsaicin-induced hyperactivity in adults. Mammalian TRPA1 is not activated by capsaicin, yet knockdown of the single predicted TRPA1-like gene (SmTRPA) in S. mansoni effectively abolishes capsaicin-induced responses in adult worms, suggesting that SmTRPA is required for capsaicin sensitivity in these parasites. Based on these results, we hypothesize that some schistosome TRP channels have novel pharmacological sensitivities that can be targeted to disrupt normal parasite neuromuscular function. These results also have implications for understanding the phylogeny of metazoan TRP channels and may help identify novel targets for new or repurposed therapeutics.